Optimization of tower-footing grounding impedance for guyed-V transmission towers - de Araújo, Anderson R.J. [UNESP] (2019)
Backflashover is one of the mechanisms by which lightning strikes can cause outages/damages in power systems. In this context, the tower-footing grounding system of transmission towers has an essential role for mitigating overvoltages that may result in backflashovers. The tower-footing grounding systems consists of long conductors, in different shapes and arrangements, buried in either homogeneous or stratified ground in order to obtain the lowest tower-footing grounding impedance. In this paper, the tower-footing grounding impedance of a typical guyed-V transmission tower is evaluated in the frequency domain using full-wave electromagnetic analysis and method of moments (MoM). Various scenarios where the tower-footing grounding system is buried in a homogeneous, a 2-, and a 3-layer stratified soil are studied. Also, the effect of the opening angle between the electrodes in the counterpoise arrangement in reducing the footing impedance is investigated. It is shown that the tower-footing impedance is notably reduced, especially when stratified soil is considered in the analysis.